Development of Vehicle-to-Everything (V2X) wireless communication application - Heng, Bang Song (Nanyang Technological University, 2022)
Vehicle-to-Everything (V2X) is a key enabling technology for safe driving and autonomous vehicle. Development in V2X wireless communication has been massively deployed in recent years due to its potential to enable a host of new applications, stemming from its potential to improve safety in road users. A safety application which utilizes V2X communication technology is Emergency Electronic Brake Light (EEBL), which provides warning to a driver when there is a hard-braking maneuver performed by a vehicle ahead of it. Upon an emergency situation where a vehicle decelerates rapidly, a hard-braking event is broadcasted via Basic Safety Message (BSM) to surrounding vehicles, where they process information through the EEBL algorithm and determine if there is danger of a rear-end collision. If deemed necessary by the algorithm, an alert which can be in the form of visual, audio, haptic or any combination thereof, is generated and immediately warns the driver who can make the most appropriate action to mitigate an accident. A timely alert is particularly helpful in cases where the brake lights of the braking vehicle are being obstructed by another vehicle, or in heavy rain and foggy conditions. The effectiveness and viability of the EEBL safety application is highly dependent on the algorithm behind identification of threats, as well as timely retrieval of vehicular information updates. This report presents the methodology of designing and implementation of EEBL application, as well as results from simulation and field testing of the application under different scenarios.